Kommunesammenlægningernes betydning for kommunalpolitikernes motivation - Dahlgaard, Jens Olav; Pedersen, Lene Holm (Politik, 2010)
This paper examines the impact of the major Danish municipal amalgamations of 2007 on the motivational bases for politicians in local government. The focus is narrowed down to Public Service Motivation (PSM), a form of altruistic motivation present in the provision of public services. Two subdimensions of PSM, Public Interest and User Orientation, are used. The analysis shows that Public Interest is unaffected by amalgamation degree, while User Orientation is negatively affected. In other words, the councillors, who have experienced the highest degrees of amalgamation, have the lowest degree of User Orientation.